Resumption of anticoagulant therapy after anticoagulant-related gastrointestinal bleeding: A systematic review and meta-analysis. Issue 175 (March 2019) - Little, D.; Chai-Adisaksopha, C.; Hillis, C.; Witt, D.M.; Monreal, M.; Crowther, M.A.; Siegal, D.M.
Abstract: Introduction: Oral anticoagulation (OAC) is permanently discontinued in up to 50% of patients following a gastrointestinal (GI) bleed. A previous meta-analysis showed a reduced risk of thromboembolism and death, and a non-statistically significant increased risk of re-bleeding associated with resumption. We conducted an updated meta-analysis to determine the risks of recurrent GI bleeding, thromboembolism, and death in patients who resumed OAC compared to those who did not. Materials and methods: We searched EMBASE, MEDLINE, and the Cochrane Central Register of Controlled Trials for new references from January 2014 to September 2017. Randomized controlled trials and observational studies involving adults with OAC-related GI bleeding were included. Risk of bias was assessed using the Cochrane Collaboration's ROBINS-I tool. Pooled relative risk (RR) ratios were calculated using a random-effects model. Results: We identified 12 observational studies involving 3098 patients. There was an increased risk of recurrent GI bleeding (RR 1.91, 95% CI 1.47–2.48, I 2  = 0%, 11 studies), and a reduced risk of thromboembolism (RR 0.30, 95% CI 0.13–0.68, I 2  = 59.8%, 9 studies) and death (RR 0.51, 95% CI 0.38–0.70, I 2  = 71.8%, 8 studies) in patients who resumed OAC compared to those who did not. Eleven studies were judged to be at serious risk of bias due to confounding. Conclusions: Resuming OAC after OAC-related GI bleeding appears to be associated with an increase in recurrent GI bleeding, but a reduction in thromboembolism and death. Further prospective data are needed to identify patients for whom the net clinical benefit favours OAC resumption and the optimal timing of resumption. Highlights: 40% of oral anticoagulant (OAC)-related bleeds are gastrointestinal (GI) bleeds. OAC is discontinued in 41–51% of patients after a GI bleed. Resuming OAC is associated with an increased risk of recurrent GI bleeding. Resuming OAC is associated with a reduced risk of thromboembolism and mortality.